Does Foreign Ownership Amplify the Impacts of Environmental Management System and Environmental Cost on ASRRAT? - Dwi Jayanti; Alya Putri Cellya (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2026)
Nowadays, firms are expected to demonstrate both financial performance and environmental accountability, increasing the importance of sustainability reporting quality. Nevertheless, internal environmental efforts do not necessarily result in better reporting outcomes, and the role of ownership structure remains underexplored. This study examines the effects of Environmental Management System (EMS) and Environmental Cost (EC) on the Asia Sustainability Reporting Rating (ASRRAT), involving Foreign Ownership as a moderating variable. The sample comprises 11 firms that consistently participated in ASRRAT from 2018 to 2024, resulting in 77 firm-year observations. Secondary data were collected from annual reports, sustainability reports, and records from the National Center for Corporate Reporting (NCCR). Ordinal logistic regression was used in the analysis, measuring ASRRAT as an ordered categorical variable. The results show that both EMS and EC positively affect ASRRAT. Similarly, Foreign Ownership also has a positive direct effect on ASRRAT. Furthermore, it strengthens the relationship between EMS and ASRRAT, but it does not significantly moderate the relationship between Environmental Cost and ASRRAT. These findings suggest that effective internal systems, supported by stronger external monitoring, can improve the quality of sustainability reporting.